Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Contextual Teaching And Learning Pada Materi Thaharah Di MTs Al-Muttaqiin Besitang - Arlina Arlina; A Zeni Azima; Diky Ananta Sembiring; Juan Adji Rizky; Hiayatul Fikri Koto (LPPM Politeknik Pratama, 2023)
This study aims to determine the learning process using the contextual teaching and learning model on thaharah material in class VII MTs Al-Muttaqiin Besitang and to see the use of this media will improve learning outcomes that affect students' self-change. The research method used is Classroom Action Research (PTK) or Classroom Action Research where this research has a very important role and a strategy to improve the quality of learning if implemented properly and correctly. The research results explain that thaharah learning in class VII MTS Al-Muttaqiin is dominated by teachers using less varied learning methods. Teachers often use the lecture method. The learning process in this study was carried out with the stages of classroom action research namely planning, action/implementation, observation, and reflection. The increase in student learning cooperation can be seen from the student cooperation questionnaire which was carried out in just 2 cycles using the pretest and posttest questionnaires at one meeting